Capillary force assisted fabrication of DNA templated silver wires - Vengadesh, P.; Ciniciato, G.P.M.K.; Zhijian, C.; Musoddiq, M.; Fisher, A.C.; Yunus, K. (Royal Society of Chemistry, 2015)
We demonstrate for the first time the formation of micron scale conductive silver (Ag) wires induced by capillary forces through scribed micro-cuts on a deoxyribonucleic acid-silver nanoparticle (DNA-AgNPs) film. The "writing" flexibility based on the physical re-arrangement of the particles may prove to be prominent towards the fabrication of conductive wires.